Effects of ellipticity angle on soliton solutions and modulation instability spectra in two-core birefringent optical fibers - Depelair, Bienvenue; Douvagai; Houwe, Alphonse; Betchewe, Gambo; İnç, Mustafa; Doka, Serge Y. (Springer, 2021)
In this paper, we investigate a coupled nonlinear Schrodinger equation which describes the propagation the propagation of optical signal in a two core optical fiber. A rich variety of various types of solitary wave solutions are exhibited including dark, bright, dark-bright, kink, anti-kink, singular, combined singular, triangular periodic solutions, Jacobi elliptic function solutions, combined Jacobi elliptic function solutions and periodic singular wave soliton solutions are obtained through the auxiliary equation method. We also investigate the modulation instability (MI) in the considered system. The study of the MI gain spectrum is done in the normal and anomalous dispersive regimes. To show the real physical significance of the studied equations, some three dimensional (3D) and two dimensional (2D) figures of obtained solutions are plotted with the use of the Matlab software under the proper choice of arbitrary parameters.
Keywords: Coupled nonlinear Schrodinger equations; Solitary wave solutions; Modulation instability